Enhancing Immune Response and Heterosubtypic Protection Ability of Inactivated H7N9 Vaccine by Using STING Agonist as a Mucosal Adjuvant - Luo, Jian; Liu, Xu-ping; Xiong, Fei-fei; Gao, Fei-xia; Yi, Ying-lei; Zhang, Min; Chen, Ze; Tan, Wen-song (Frontiers in Immunology, 2019)
Influenza vaccines for H7N9 subtype have shown low immunogenicity in human clinical trials. Using novel adjuvants might represent the optimal available option in vaccine development. In this study, we demonstrated that the using of the STING agonist cGAMP as a mucosal adjuvant is effective in enhancing humoral, cellular and mucosal immune responses of whole virus, inactivated H7N9 vaccine in mice. A single dose of immunization was able to completely protect mice against a high lethal doses of homologous virus challenge with an significant dose-sparing effect. We also found that intranasal co-administration of H7N9 vaccine with cGAMP could provide effective cross protection against H1N1, H3N2, and H9N2 influenza virus. Furthermore, cGAMP induced significantly higher nucleoprotein specific CD4+ and CD8+ T cells responses in immunized mice, as well as upregulated the IFN-γ and Granzyme B expression in the lung tissue of mice in the early stages post a heterosubtypic virus challenge. These results indicated that STING agonist cGAMP was expected to be an effective mucosal immune adjuvant for pre-pandemic vaccines such as H7N9 vaccines, and the cGAMP combined nasal inactivated influenza vaccine will also be a promising strategy for development of broad-spectrum influenza vaccines.